Strategic fire zones are essential to wildfire risk reduction in the western United States - North, Malcolm P., author; Bisbing, Sarah M., author; Hankins, Don L., author; Hessburg, Paul F., author; Hurteau, Matthew D., author; Kobziar, Leda N., author; Meyer, Marc D., author; Rhea, Allison E., author; Stephens, Scott L., author; Stevens-Rumann, Camille S., author; Springer Nature, publisher (Colorado State University. Libraries, 2024)
Background Over the last four decades, wildfires in forests of the continental western United States have significantly increased in both size and severity after more than a century of fire suppression and exclusion. Many of these forests historically experienced frequent fire and were fuel limited. To date, fuel reduction treatments have been small and too widely dispersed to have impacted this trend. Currently new land management plans are being developed on most of the 154 National Forests that will guide and support on the ground management practices for the next 15 20 years. Results During plan development, we recommend that Strategic Fire Zones (SFZs) be identified in large blocks (? 2,000 ha) of Federal forest lands, buffered (? 1 2.4 km) from the wildland-urban interface for the reintroduction of beneficial fire. In SFZs, lightning ignitions, as well as prescribed and cultural burns, would be used to reduce fuels and restore ecosystem services. Although such Zones have been successfully established in a limited number of western National Parks and Wilderness Areas, we identify extensive remote areas in the western US (8.3 12.7 million ha), most outside of wilderness (85 88%), where they could be established. Potential wildland fire Operational Delineations or PODs would be used to identify SFZ boundaries. We outline steps to identify, implement, monitor, and communicate the use and benefits of SFZs. Conclusions Enhancing collaboration and knowledge-sharing with Indigenous communities can play a vital role in gaining agency and public support for SFZs, and in building a narrative for how to rebuild climate-adapted fire regimes and live within them. Meaningful increases in wildland fire use could multiply the amount of beneficial fire on the landscape while reducing the risk of large wildfires and their impacts on structures and ecosystem services.
Keywords: firefighter work force; forest resilience; Indigenous burning; lightning-ignited fire; prescribed fire; wildfire smoke